Lignin chemistry and applications - Huang, Jin (Biochemist); Fu, Shiyu; Gan, Lin (Chemical engineer) (Chemical Industry Press series. Series on natural polymer based novel materials, 2019)
Lignin Chemistry and Application systematically discusses the structure, physical and chemical modification of lignin, along with its application in the field of chemicals and materials. It presents the history of lignin chemistry and lignin-modified materials, describes recent progresses, applications and studies, and prospects the development direction of high value applications of lignin in the field of material science. In addition to covering the basic theories and technologies relating to the research and application of lignin in polymer chemistry and materials science, the book also summarizes the latest applications in rubber, engineering plastics, adhesives, films and hydrogels.